1985
DOI: 10.1007/bf00735728
|View full text |Cite
|
Sign up to set email alerts
|

Shunt placement and myelomeningocele repair: simultaneous vs sequential shunting

Abstract: The optimal management of patients with myelomeningocele and hydrocephalus is facilitated by a constant review of the patients with the aid of the sonogram and CT scan. Six infants treated with simultaneous shunt placement and myelomeningocele repair were compared with six other neonates treated with conventional sequential myelomeningocele repairs requiring a second separate procedure for shunt placement. Infants operated upon simultaneously experienced no increase in morbidity or mortality and appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
3
16
0
1
Order By: Relevance
“…Epstein et al [16] were the first to advocate simulta neous closure and shunting of the infant born with my elomeningocele and overt hydrocephalus. Other authors have subsequently endorsed the selective simultaneous shunting of spina bifida infants with hydrocephalus [15][16][17][18][19][20], Several studies have noted that the spina bifida child presenting with hydrocephalus is more likely to have a higher sensory level and a larger myelomeningocele than the normocephalic spina bifida infant [15,16,19].…”
Section: Discussionmentioning
confidence: 99%
“…Epstein et al [16] were the first to advocate simulta neous closure and shunting of the infant born with my elomeningocele and overt hydrocephalus. Other authors have subsequently endorsed the selective simultaneous shunting of spina bifida infants with hydrocephalus [15][16][17][18][19][20], Several studies have noted that the spina bifida child presenting with hydrocephalus is more likely to have a higher sensory level and a larger myelomeningocele than the normocephalic spina bifida infant [15,16,19].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with frank hydrocephalus, concurrent placement of a shunt at the time of myelomeningocele repair is considered safe and seems to not increase the rate of complications. 3,14,21,29,42 For patients with asymptomatic ventriculomegaly at birth, the timing of shunt placement is controversial. Some have suggested that a watch-and-wait strategy may reduce the overall rate of shunting in this group, but the risk for CSF leakage from the surgical repair site might be increased.…”
Section: Hydrocephalusmentioning
confidence: 99%
“…Many authors have suggested the repair of MM and shunt insertion during same session (4,10,12,20). According to them, in patients with HCP and MM, insertion of shunt in same session would provide a swift recovery of back, avoid a second operation, protect the brain from deterious effects of progressive HCP resulting from delayed shunting and decrease duration of hospitalization (7,10,15,20,23). However, there is also an opposite view; concurrent shunt surgery, in same session, may cause an increased shunt infection risk, which is a common complication of shunting in the patients with MM, observed between the rates of 2-39% (18), because ventricular shunt placement reverses cerebrospinal fluid (CSF) flow from the lumbar region to ventricles (3,9,18).…”
Section: Introductionmentioning
confidence: 99%